2021
DOI: 10.3389/fmed.2021.787777
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cholecystectomy With Liver Fibrosis and Cirrhosis Among Adults in the USA: A Population-Based Propensity Score-Matched Study

Abstract: Background and Aims: Cholecystectomy is the “gold standard” for treating diseases of the gallbladder. In addition, non-alcoholic fatty liver disease (NAFLD), liver fibrosis or cirrhosis, are major causes of morbidity and mortality across the world. However, the association between cholecystectomy and these diseases is still unclear. We assessed the association among US adults and examined the possible risk factors.Methods: This cross-sectional study used data from 2017 to 2018 National Health and Nutrition Exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
(53 reference statements)
1
12
0
Order By: Relevance
“…We previously studied the relationship of NAFLD with gallstone disease using NHANES 1988-1994 and found that in the US population, NAFLD was associated with cholecystectomy, but not gallstones 40. An association of cholecystectomy with liver fibrosis and cirrhosis defined by liver stiffness was reported using NHANES 2017-2018 41. However, the direction of relationships cannot be determined with certainty using cross-sectional survey data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously studied the relationship of NAFLD with gallstone disease using NHANES 1988-1994 and found that in the US population, NAFLD was associated with cholecystectomy, but not gallstones 40. An association of cholecystectomy with liver fibrosis and cirrhosis defined by liver stiffness was reported using NHANES 2017-2018 41. However, the direction of relationships cannot be determined with certainty using cross-sectional survey data.…”
Section: Discussionmentioning
confidence: 99%
“…[40] An association of cholecystectomy with liver fibrosis and cirrhosis defined by liver stiffness was reported using NHANES 2017-2018. [41] However, the direction of relationships cannot be determined with certainty using cross-sectional survey data. Current alcohol use was associated with lower odds of gallstone disease after accounting for other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Cholecystectomy and MASLD are two of the most common medical conditions when we refer to the gastrointestinal tract. Although the studies published on both topics are not usually linked to each other, there is evidence that cholecystectomy may worsen the course of MASLD [ 50 , 51 , 52 ]. Cholecystectomy has also been considered an independent risk factor for MASLD [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the search was extended to NAFLD definition, some contradictory studies were observed, but most of them considered cholecystectomy to be a risk factor for liver fibrosis. Xie et al [ 52 ] performed a study including almost 5000 patients, in which a positive correlation was concluded between cholecystectomy and liver fibrosis. Kichloo et al [ 74 ] conducted a study in hospitalized patients in which it was obtained as a result that cholecystectomy and gallstone disease may be risk factors for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression models have also been used to create predictive algorithms that describe the probability of an event using nomograms or online calculators, such as assessment of fibrosis and prediction of survival of patients with HCC [139][140][141]. Alternatively, logistic regression models have been applied to calculate propensity scores, which can be used to adjust the imbalance of baseline confounders between two cohorts when the goal is to compare their identical outcomes [142,143]. Furthermore, because the outcome variables are binary, logistic regression can be used for binary classification tasks.…”
Section: Logistic Regressionmentioning
confidence: 99%